Complementary food introduction practices in infants with intestinal failure. (28th June 2022) - Nucci, Anita M.; Samela, Kate; Bobo, Elizabeth; Wessel, Jacqueline
Abstract: Background: Oral intake in infants with intestinal failure (IF) may be limited due to intolerance or feeding difficulties. Guidelines for the introduction of semisolid or solid complementary foods (CFs) to infants with IF do not exist. CF intake and caloric contribution from CF is difficult to assess due to malabsorption and incomplete recording. The aim of this study was to identify institutional approaches to introducing CF to infants with IF. Methods: The American Society for Parenteral and Enteral Nutriton (ASPEN) Pediatric Intestinal Failure Section Registered Dietitian/Nutritionist (RDN) working group designed a 10‐question online cloud‐based survey to assess group member practice related to the introduction of CF to infants with IF. Results: Twenty‐six surveys were completed. Thirteen (50%) RDNs recommend introduction of CF between 4 and 6 months of age. Nineteen (76%) recommend adding pureed foods to gastrostomy tube feedings. Seventeen (65%) follow standard infant feeding practice guidelines with half citing the American Academy of Pediatrics. Approximately half (44%) recommend introducing vegetables first and the majority (80%) recommend delaying the introduction of fruits. The vast majority (92%) recommend specific foods to minimize stool output including green beans, bananas, infant cereals, and meats/protein. Conclusion: Institutional practices related to the introduction of CF to infants with IF vary. Similarities with first food choice and foods to avoid were observed. Evidenced‐based practice guidelines for the introduction of CF to infants with IF need to be established to determine best practices for reducing stool output, encouraging weaning from parenteral nutrition, and achieving enteral autonomy.